Regulating facility soil microbial community and reducing cadmium enrichment in lettuce by reductive soil disinfestation - Sun, Kaining; Zhang, Shu; Wang, Junfeng (Frontiers in Environmental Science, 2024)
The accumulation of cadmium (Cd) in facility soil is attracting increasing attention. Reductive soil disinfestation (RSD) is an effective soil disinfection method, while also having a certain passivating effect on Cd. The application of organic matter is crucial for the success of RSD, but the reduction efficiencies of different organic materials vary. Here, five treatments, namely untreated soil (CK), bean dregs (BD), peanut dregs (PD), sesame dregs (SD), and apple dregs (AD) were applied, and their performances in Cd immobilization in Cd-contaminated soil were assessed. Changes in soil properties and microbial communities were monitored. The results showed that the overall soil pH following RSD treatment decreased significantly, while organic matter, hydrolyzed nitrogen, available phosphorus, available potassium, exchangeable calcium, and exchangeable magnesium increased significantly. Compared to CK, the exchangeable (EX)-Cd contents after treatments SD and AD significantly decreased by 25.4% and 23.7%, respectively. RSD led to significant changes in the composition of soil microbial communities. SD treatment significantly increased the number of soil fungal operational taxonomic units (OTU), while BD, PD, and SD significantly increased the relative abundances of Bacteroidetes, Chloroflexi, Deinococus Thermus, and Basidiomycota in bacterial communities. The Gemmatimonadetes phylum showed a highly significant negative correlation with EX-Cd, indicating that it might have a positive effect on the fixation of Cd in polluted soil. SD significantly reduced the Cd content in the above-ground parts of lettuce by 74.76%, and had the least impact on lettuce biomass. It can be inferred that RSD is an ecologically effective method for the remediation of Cd pollution in facility soil by improving soil characteristics and altering microbial community composition to reduce Cd activity. However, further in-depth research is needed to optimize the types and amounts of organic materials applied.